Breast Fistula Repair after Autologous Fat Graft: A Case Report. (7th June 2011) - Klinger, Francesco Maria; Caviggioli, Fabio; Forcellini, Davide; Vinci, Valeriano; Maione, Luca; Pajardi, Giorgio; Klinger, Marco
Abstract : We report the case of a 55-year-old female patient who attended our clinic for the presence of a scar retraction in the upper pole of the left breast as a complication of breast augmentation. In the scar area, we observed an orifice that probing revealed to be a fistula. The patient was referred to surgical intervention under general anesthesia to obtain scar contracture release using autologous fat graft; one month after autologous fat injection, following healing of the fistula, the patient underwent a second surgical procedure to replace the left breast implant. Unexpectedly, two weeks after the surgical procedure, complete healing of the breast fistula within the scar area was observed; this observation was confirmed during the second surgical step for left breast implant repositioning, when we observed the absence of the fistula orifice in the breast implant cavity. Upon clinical examination at 1-year followup, tissue integrity was preserved. The patient's satisfaction was excellent. We have observed a possible additional effect of fat graft.